2021
DOI: 10.4239/wjd.v12.i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Role of ferroptosis in the process of diabetes-induced endothelial dysfunction

Abstract: BACKGROUND Endothelial dysfunction, a hallmark of diabetes, is a critical and initiating contributor to the pathogenesis of diabetic cardiovascular complications. However, the underlying mechanisms are still not fully understood. Ferroptosis is a newly defined regulated cell death driven by cellular metabolism and iron-dependent lipid peroxidation. Although the involvement of ferroptosis in disease pathogenesis has been shown in cancers and degenerative diseases, the participation of ferroptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 31 publications
1
70
0
Order By: Relevance
“…It is widely accepted that disruption of local angiogenesis is a crucial limiting factor in diabetic wound healing [ 5 , 27 , 36 ]. Endothelial dysfunction seen with diabetic vascular complications results in impaired repair and abnormal angiogenesis [ 37 ]. Increasing evidence has revealed that hyperglycemia-induced impairment of endothelial cell function is an important cause of vascular dysfunction, which results in the occurrence of diabetic complications [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that disruption of local angiogenesis is a crucial limiting factor in diabetic wound healing [ 5 , 27 , 36 ]. Endothelial dysfunction seen with diabetic vascular complications results in impaired repair and abnormal angiogenesis [ 37 ]. Increasing evidence has revealed that hyperglycemia-induced impairment of endothelial cell function is an important cause of vascular dysfunction, which results in the occurrence of diabetic complications [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial dysfunction is thought to be one of the major causes of DCM (87). Recently, Luo et al (88) found that high glucose induces ferroptosis in human umbilical vein endothelial cells (HUVECs) and concluded that ferroptosis is involved in endothelial dysfunction via p53-xCT (the substratespecific subunit of system xc − )-GSH axis, suggesting that ferroptosis might participate in the process of DCM.…”
Section: Ferroptosis and Cardiovascular Diseases Ferroptosis And Cardiomyopathymentioning
confidence: 99%
“…All of the above discoveries foreshadow that ferroptosis may participate in the development of osteoporosis, especially the devitalization of osteoblasts. Recently, a study indicated that extracellular vesicles derived from endothelial progenitor cells (EPC-EVs) satisfied the need of retarding the progress of steroid-induced osteoporosis (SIOP) by inhibiting ferroptosis, specifically by reversing the deactivation of GPX4, system Xc-and decreased cysteine levels, which is initiated by dexamethasone (Lu et al, 2019). Since these speculations are based on bioinformatics evidence, the detailed signal pathways and in vitro and in vivo experiments warrant further investigation.…”
Section: Ferroptosis and Osteoporosismentioning
confidence: 99%
“…Another study sustained these results. Due to the ferroptosis-induced role played by glucocorticoids in osteoblasts (Lu et al, 2019), Yang et al (2021) originally found that exosomes derived from vascular endothelial cells (EC-Exos) counteract this process both in vitro and in vivo by decreasing NCOA4 expression to suppress ferritinophagy and simultaneously targeting the Keap1-Nrf2-HO-1/NQO-1 pathway to inhibit lipid oxidation, though the specific signal has not yet been elucidated. Some drugs that target osteoporosis may actualize a ferroptotic role during the therapeutic mechanism, which, in our perspective, is reasonable to surmise, but not yet visible.…”
Section: Ferroptosis and Osteoporosismentioning
confidence: 99%